Evaluation of artemisinin-based combination therapy (ACT) to uncomplicated falciparum malaria patients in Purworejo District, Central Java, Indonesia - Michael Bhadi Bia; E. Elsa Herdiana Murhandarwati; Neil F Lobo; William A Hawley; . Supargiyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Artemisinin-based Combination Therapy (ACT) to treat uncomplicated Plasmodiumfalciparum malaria has been applied in Purworejo District, Central Java, Indonesia, since2004. However evaluation of the two ACT regimens used ie: Artesunate Amodiaquine(AAQ) and Dihydroartemisinin-Piperaquine (DHP) co-administered with Primaquine (PQ)has not been performed. This study aims to evaluate the efficacy and side effects ofAAQ+PQ and DHP+PQ treatment in uncomplicated falciparum malaria in Purworejo. Inthis descriptive and observational study, 46 Pf infected patients who fullfill the inclusionand exclusion criterias were recruited from December 2010 to August 2011. StandardACT treatment were given to the patients followed by WHO drug efficacy evaluation for28 days. The clinical symptoms and adverse events was also evaluated over the course ofthe treatment. From all recruited subjects, 37 patients received DHP+PQ and 9 patientsreceived AAQ+PQ. On the DHP+PQ treated patient, all subjects were free of asexualand sexual parasites by Day-3 while on AAQ+PQ treated patient, this parasite clearancewas achieved faster as early as on D-2 at the latest. On the otherhand, the disappearanceof fever was also last longer in DHP+PQ treated patient which in one patient last onD-14, while in AAQ+PQ treated patient, the symptom of fever dissappeared by D-2at the latest. No Early or Late Treatment Failures were found on either DHP+PQ orAAQ+PQ treatment as well as clinical and parasitological failures. However, the presenceof adverse events cause by both drugs should not be ignored to ensure drug compliance.